Síntese e avaliação das atividades fitotóxicas e citotóxicas de compostos análogos aos nostoclídeos - Robson Ricardo Teixeira (2008)
The nostoclides are produced by a cyanobacterium Nostoc sp. symbiont of Peltigera canina, and belong to a family of compounds know as -alkylidenebutenolides. Nostoclides have been shown to have moderate cytotoxicity against the mouse neuroblastoma cell lines Neuro-2a CCL and KB CCL 17. Due to the fact that Peltigera canina cultures are usually not contaminated with microorganisms, it has been suggested that these chlorinated compounds may be allelopathic agents. As consequence, these secondary metabolites can be considered attractive as lead structure to be targeted towards the development of new chemical tools to control weeds. The present investigation aimed to synthesize a variety of nostoclides analogues and evaluate their potential phytotoxic activity. The citotoxicity of several analogues was also investigated. The synthesis of nostoclides analogues, namely 3-benzyl-5-arylmethylene furan-2(5H)-ones, was accomplished via the vinylogous aldol reaction between appropriate aldehydes and furan-based silyloxy diene synthon generated from 3-benzyl-furan-2(5H)-one. This lactone, in turns, was prepared from furan-2(5H)-one. Thus, the treatment of 3-benzylfuran- 2(5H)-one with tert-butyldimethylsilyl trifluoromethanesulfonate and diisopropylethylamine, in the presence of appropriate aldehydes, followed by treatment of the silyl ether generated in situ with DBU afforded 35 nostoclides analogues in yields varying from 12-91%. The structures of nostoclides analogues were confirmed based on NMR, IR and MS analyses. In all cases, the presence of molecular ion peak was observed in the MS spectra, which correlated with the expected molecular formulas. A combination of two dimensional NMR analyses (HSQC and HMBC) of the lactones synthesized not only confirmed the presence of the five membered ring ,-unsaturated lactone moiety, substituted by both the benzyl and benzylidene functionalities, but also allowed complete hydrogen and carbon assignments. The biological activity of the synthesized 3-benzyl-5-arylmethylene furan-2(5H)-ones was evaluated in vitro as the ability to interfere with light-driven reduction of ferricyanide by isolated spinach chloroplasts. About two-thirds of the compounds exhibited inhibitory properties in the micromolar range against the basal electron flow from water to K3[Fe(CN)6]. In addition, the cytotoxicity of several of these furanones was also evaluated employing the MTT assay. Besides the evaluation of phytotoxicity and cytotoxicity, the insecticidal activity of some compounds, which were either employed as synthetic intermediates or obtained as byproducts, was investigated.